Mechanistic Investigations on Reactivities of Alkanone Semicarbazones towards Chloramine-T: A Kinetic Study - Venkateswaran, V.; Asaithambi, M.; Parimala Devi, P.; Geetha, A. (Asian Journal of Chemistry, 2016)
Kinetics of oxidation of few alkanone semicarbazones by chloramine-T in aqueous acetic acid medium has been investigated in the presence of perchloric acid at 308 K. The reaction follows first order kinetics in [CAT], fractional order in [substrate], inverse fractional order in [H3O+]. Variation in ionic strength of the medium and addition of the reaction product, p-toluene sulphonamide has no effect on the rate of reaction. An increase in the rate is observed when the dielectric constant of the medium is decreased. The stoichiometries of the reactions are established, the oxidation products are identified and the relative reactivities of the various substrates have been determined. The rate limiting step has been identified, the rate coefficients of these steps and the related activation parameters have also been evaluated. The validity of the deduced rate law has been checked by recalculating the rate constants.